2019
DOI: 10.1177/2325967119s00211
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Mobilization After Superior Rotator Cuff Repair: Sling versus No-sling. A Randomized Controlled Trial: Sling versus no-sling after RCR

Abstract: Objectives: Patients are commonly advised to wear a sling for 4-6 weeks after rotator cuff repair (RCR) despite negative effects of early immobilization and benefits of motion rehabilitation. The study aimed to compare clinical and radiographic outcomes up to 6 months following RCR with sling immobilization and without sling immobilization. Methods: We randomized 80 patients scheduled for arthroscopic repair of small or medium superior rotator cuff tears into 2 equal groups: 'sling' and 'no-sling' groups. Pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 0 publications
0
41
0
2
Order By: Relevance
“…Other recent randomised controlled trials have been reported. 11,20,21 Mazzocca et al 20 ( n = 73) compared early movement (starting two to three days after surgery) versus delayed movement (starting 28 days after surgery), similar to standard rehabilitation reported here. There was no statistically significant difference in Western Ontario Rotator Cuff scores at six months, but the early movement group reported lower scores (better clinical status) throughout the post-operative period.…”
Section: Discussionmentioning
confidence: 94%
“…Other recent randomised controlled trials have been reported. 11,20,21 Mazzocca et al 20 ( n = 73) compared early movement (starting two to three days after surgery) versus delayed movement (starting 28 days after surgery), similar to standard rehabilitation reported here. There was no statistically significant difference in Western Ontario Rotator Cuff scores at six months, but the early movement group reported lower scores (better clinical status) throughout the post-operative period.…”
Section: Discussionmentioning
confidence: 94%
“…The method of immobilisation after rotator cuff repair was variable. The majority of the RCTs (3, 19, 20, 23-30)(11/20, 55%) reported the use of a standard sling, six RCTs (18, 21, 22, 31-33) used a sling with an abduction component and one RCT (34) used a standard sling for the early group and a sling with an abduction component for the delayed group. The time in the sling was also variable; eight RCTs (40%) (18, 21, 23-26, 29, 32) used a six-week period for both groups.…”
Section: Resultsmentioning
confidence: 99%
“…Three RCTs prescribed a sling for the early group to be used for comfort only and discarded as the patient felt appropriate (3, 19, 20). One RCT did not prescribe a sling for those in the early group (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, among the protocols designated for small (10 protocols) or medium (17 protocols) RTC tears, use of a postoperative sling or immobilizer was recommended for the first 4 weeks postoperatively or longer in 22 of 27 protocols (81.5%). However, in a study looking at immobilization after RTC repair, Tirefort et al 16 found that sling use may not be indicated after repair of small or medium RTC tears, owing to their finding that undergoing no immobilization was associated with better early mobility and functional scores than undergoing sling immobilization. They also determined that undergoing no immobilization was significantly associated with reduced pain and improved function at 6 months compared with patients undergoing 4 weeks of sling use or immobilization.…”
Section: Discussionmentioning
confidence: 99%